Enediyne dimerization vs Bergman cyclization - Haberhauer, Gebhard; Gleiter, Rolf; Fabig, Sven (Organic letters, 2015)
High-level quantum chemical calculations reveal that the dimerization of enediynes to 1,3-butadiene-1,4-diyl diradicals is energetically more favored than the corresponding Bergman cyclization of enediynes. Moreover, the activation barrier of both reactions can be drastically reduced by the introduction of electronwithdrawing substituents like fluoro groups at the reacting carbon centers of the triple bonds.
Gesehen am 22.02.2021